134k views
0 votes
Can someone please help right now please!!!!!!

Can someone please help right now please!!!!!!-example-1

1 Answer

6 votes

Answer:

-23

Explanation:

We are given the quotient of the numerical expression
(-48)/(-8) = 6.

Now, we want to find the value of x in the algebraic expression 6 + x = -17.

So, 6 + x = -17 → x = -17 - 6 → x = -23.

So, -23 should be added to 6 such that the sum is equal to -17.

i.e 6 + (-23) = -17.

Hence, -23 should be added to the quotient of
(-48)/(-8) so that the sum comes out to be -17.

User Rakesh Goyal
by
5.8k points